Perfluoroalkyl substances and lipid profile in exposed pregnant women in the Veneto Region, Italy. (30th September 2020) - Dalla Zuanna, T; Barbieri, G; Pitter, G; Zare Jeddi, M; Daprà, F; Savitz, D; Fabricio, A; Russo, F; Fletcher, T; Canova, C
Abstract: Background: Perfluoroalkyl substances (PFASs) are persistent and widespread environmental pollutants. Residents of a large area of the Veneto Region (North-Eastern Italy) were exposed to high concentrations of PFASs through drinking water from the late-1970s to 2013. PFASs have been consistently associated with raised serum lipids, but only few studies have been conducted among pregnant women, and none has stratified analyses by trimesters of gestation. Our main objective was to evaluate the association between perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) levels and lipid profiles in high-exposed pregnant women. Methods: A cross-sectional analysis was conducted in 319 pregnant women (age 14-48 years) recruited in the Regional health surveillance program. Serum PFASs were measured by HPLC-MS/MS. Non-fasting serum total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C) were measured by enzymatic assays in automated analysers, and low-density lipoprotein cholesterol (LDL-C) was calculated. The associations between ln-transformed PFASs (and categorized into quartiles) and lipids were assessed using generalized additive models. Analyses were adjusted for potential confounders and stratified according to pregnancy trimester. Results: In the first trimester, plasma concentrations of both PFOA and PFOS were positively associated with TC. However in the third trimester PFOA levels were instead inversely significantly associated with TC and LDL-C levels. Overall, both PFOA and PFOS were positively associated with HDL-C, and PFOA negatively with LDL-C. Conclusions: In a small highly exposed population of pregnant women, the associations between PFASs concentrations and lipid profile were modified by trimester of gestation. Patterns late in pregnancy were different to the positive associations with LDL-C generally found. Differential transfer and bioaccumulation of lipids and PFAS in the placenta across gestation might explain our findings. Key messages: This study provides evidence of different patterns of PFAS associations with lipids in pregnant women across the trimesters of gestation. The different patterns of association from general population studies sheds light on the role of fetal nutrition during pregnancy affecting both lipids and PFAS in serum.